Relación de la red de drenaje y la evolución hipsométrica con las características morfométricas de la subcuenca del río Carrizal - Risco Cedeño, Karla Patricia (2023)
Worldwide, the dependencies that populations maintain in relation to water focus mainly on the development, knowledge and care of this resource. This research is framed as a contribution to local knowledge in order to make decisions on the issues of territorial planning, flood control, civil protection, infrastructure and public policies, in order to work together to strengthen local and institutional capacities. For this purpose, a digital elevation model (DEM) was obtained from the SIGTIERRAS platform, which was processed in the Q-GIS software to obtain the drainage direction layers, accumulated draining cells and Beven index. With this, the Carrizal sub-basin was limited and the drainage network was identified for its characterization and comparison with the morphometric characteristics of the basin and the hypsometric profile. The basin area was established at 1,329.63 km2 and the perimeter at 251.6 km; the Carrizal River was identified as the main channel with a length of 80.66 km. According to the shape indicators, the basin was categorized as rectangular or elongated. The hypsometric curve showed that it is an old or sedimentary basin due to its convex shape, that is, it has undergone a long process of erosion. These results give way to the planning of water resource management and ordering policies, which, in turn, involves soil management and care of vegetation cover.